Design of Fiber Optic Load Sensor for Low-Load Detection Using Microbending Method - Setiono, Andi; Tarigan, Kerista; Baruara, Lamrouli (Talenta Publisher, 2023)
This research aimed to design and investigate the fiber optic load sensor produced from the mixture of 100 mesh grains of sand, silicone rubber, and catalyst. The response of the resulted fiber optic load sensor was measured by detecting the microbending of single-mode fiber optic in the form of the power meter. The test was conducted using a light source as an input signal on the sensor. The laser is stable for each load sensor test, with a wavelength of 1500 nm. The study's results confirmed that the load sensor's response has a connection between the amount of load and the voltage; the greater the pressure or load, the less the output power will decrease and cause signal weakening.